The importance of directly derived information in the basketball jump shot. A comparison of changed visual conditions from different shooting spots - Pohl, A.; Böker, M.; Hennig, L.; Heinen, T. (Central European Journal of Sport Sciences and Medicine, 2017)
The basketball jump shot as a movement, allowing visual feedback based corrections, can be considered as a generalized or a specialized motor skill. The purpose of this study is to look into the connection between visual perception and the specialization of a motor skill. Therefore, six male basketball players were asked to perform jump shots under different viewing conditions from their favourite spot (sweet spot) and a second, middle-distance spot. The question was, if performance is affected by the changed visual conditions and whether the shooting spot plays a role in a potentially change in performance. The different visual conditions were first, a regular basketball hoop with no adjustment, second a regular basketball hoop with a covered backboard, and third a regular basketball hoop with a covered rim. Between the different visual conditions, performance did not differ significantly, neither from the sweet spot, nor from the neutral defined spot. However, players showed a significantly better performance from sweet spot than from the neutral spot under regular viewing conditions.